Targeting the PD-1/PD-L1 Immune Evasion Axis With DNA Aptamers as a Novel Therapeutic Strategy for the Treatment of Disseminated Cancers - Aaron Prodeus; Aws Abdul-Wahid; Nicholas W Fischer; Eric H-B Huang; Marzena Cydzik; Jean Gariépy (Elsevier, 2015)
Blocking the immunoinhibitory PD-1:PD-L1 pathway using monoclonal antibodies has led to dramatic clinical responses by reversing tumor immune evasion and provoking robust and durable antitumor responses. Anti-PD-1 antibodies have now been approved for the treatment of melanoma, and are being clinically tested in a number of other tumor types as both a monotherapy and as part of combination regimens. Here, we report the development of DNA aptamers as synthetic, nonimmunogenic antibody mimics, which bind specifically to the murine extracellular domain of PD-1 and block the PD-1:PD-L1 interaction. One such aptamer, MP7, functionally inhibits the PD-L1-mediated suppression of IL-2 secretion in primary T-cells. A PEGylated form of MP7 retains the ability to block the PD-1:PD-L1 interaction, and significantly suppresses the growth of PD-L1+ colon carcinoma cells in vivo with a potency equivalent to an antagonistic anti-PD-1 antibody. Importantly, the anti-PD-1 DNA aptamer treatment was not associated with off-target TLR-9-related immune responses. Due to the inherent advantages of aptamers including their lack of immunogenicity, low cost, long shelf life, and ease of synthesis, PD-1 antagonistic aptamers may represent an attractive alternative over antibody-based anti PD-1 therapeutics.